Biased Lewis Pairs: A General Catalytic Approach to Ether‐Ester Block Copolymers with Unlimited Ordering of Sequences. Issue 43 (18th September 2019) - Liu, Shan; Bai, Tianwen; Ni, Kang; Chen, Ye; Zhao, Junpeng; Ling, Jun; Ye, Xiaodong; Zhang, Guangzhao
Abstract: Polymerizing epoxides after cyclic esters remains a major challenge, though their block copolymers have been extensively studied and used for decades. Reported here is a simple catalytic approach based on a metal‐free Lewis pair that addresses the challenge. When the Lewis acid is used in excess of a base, selective (transesterification‐free) polymerization of epoxides occurs in the presence of esters, while selectivity toward cyclic esters is achieved by an oppositely biased catalyst. Hence, one‐pot block copolymerization can be performed in both ester‐first and ether‐first orders with selectivity being switchable at any stage, yielding ether‐ester‐type block copolymers with unlimited ordering of sequences as well as widely variable compositions and architectures. The selectivity can also be switched back and forth several times to generate a multiblock copolymer. Experimental and calculational results indicate that the selectivity originates mainly from the state of catalyst‐activated hydroxy species. Abstract : Mixer event : A two‐component metal‐free catalytic system comprising a Lewis acid and base in unequal molar amounts allows monomer‐selective and switchable polymerization of mixed epoxides and cyclic esters. The method challenges the existing limitation of the enchainment order of the two types of monomers and fulfills sequence‐controlled synthesis of ether‐ester‐type block copolymers.